Assessment of general well-being before and after treatment for morbidities among inmates of a destitute centre of north Karnataka: a pre and post evaluation study - Desai, Sachin; Metgud, Chandra S. (International Journal Of Community Medicine And Public Health, 2017)
Background: The destitute centre was established in 1992, 14th August; situated in Karnataka with a built up area is 29 acres and has 33 males and 17 female inmates. The patients here can be classified as having psychiatric illness, destitute with general co morbid conditions and wandering tramps with normal mentation. The study was done to know the morbidity profile among the inmates of destitute centre and to assess the change in the quality of life before the morbidity assessment and after medication and treatment. Methods: It was a pre-post evaluation study done from August 2012 to December 2012. All of the 50 resident inmates of the destitute centre were evaluated before and after clinical examination and treatment with General Well Being Scale (GWBS). Results: Among the total inmates, 06 (12%) were in age group 20-29 years, 11 (22%) belonged to 30-39 years, 10 (20%) belonged to 40-49 years, 09 (18%) each belonged to 50-59 and 60-69 years age group respectively, 04 (8%) belonged to 70-79 years and 01 (2%) of the elderly belonged to age ≥80 years of age. 38 (76.0%) were males and 12 (24%) were females. Majority of the inmates i.e. 42 (84.0%) belonged to broken families, about 4(8.0%) elderly belonged to problem families. 18 (36.0%) consumed tobacco, about 07 (14.0%) were either smoking or consuming alcohol, about 02 (4.0%) had both alcohol and smoking habits. Conclusions: 74% of them had psychiatric comorbidities and these were likely to cause significant functional impairment. Appropriate treatment helped 5 (10%) individuals to be shifted to rehabilitation center.